Comparison of aftershock behavior of the flores sea 12 december 1992 and 14 december 2021 - Jufriansah, Adi; Khusnani, Azmi; Pramudya, Yudhiakto; Afriyanto, Mulya (Journal of Physics: Theories and Applications, 2023)
Over 30 years, the Flores region experienced earthquakes with Mw >7 twice, namely in 1992 and 2021 at shallow depths <60 km. However, the behavior of the aftershocks accompanying the quake has yet to be studied in detail. This research aims to compare the behavior of aftershocks after the main earthquake. This research uses three-lifetime analysis functions, namely, Wilber3, Mustang Web Browser, and comparison of Probability Density Function Hazard. The data used comes from IRIS data and BMKG Online Data. Through graphical analysis, it is known that the data for the time difference for aftershocks follow the RMS distribution, indicating that the Flores Sea aftershock on 12 December 1992 occurred with high intensity on the 3rd and the 6th day after the main earthquake. Meanwhile, the aftershocks in the Flores Sea on 14 December 2021 tended to occur with a more even intensity during the observation period, but the power returned to high on the 7th day